Machinability analysis of VAT 32® nickel based superalloy using commercial and experimental milling inserts - Callisaya, Emanuele Schneider [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Over the past decades, the superalloy metallurgy industry has made possible many innovations with high impact to the metal-mechanic industry. However, currently, these industries have to cope with both the technical and commercial challenges of new rigid environmental regulations. In this scenario, due to a more restrict series of environmental requirements, a new nickel intermediate superalloy designated VAT 32® was developed for application in automotive high performance valves. The VAT 32® superalloy presents high wear and high temperatures resistance and lower production costs if compared to traditionally applied superalloys. However, due to its chemical composition and microstructure, serious difficulties are observed in its machining process, making it very difficult to machine and limiting its application. Therefore, in order to study the machinability of the VAT 32® new superalloy considering the milling process, the present research work evaluated the alloy’s machinability by applying experimental alumina-based ceramic cutting tools (Al2O3-MgO) developed by the research group of the Materials and Technology Department of the São Paulo State University (UNESP), in comparison to TiAlN-TiN PVD-coated commercial carbide tools. The machining process output variables analyzed were power consumption, vibration, acoustic emission, resulting surface quality (roughness Ra, Rt and Rz), tools wear, chip formation and the specific cutting pressure (Ksm). To evaluate the main effects in machining it was applied the analysis of variance (ANOVA) and normality tests conducted according the design of experiments of Full-Factorial methodology. The dry finishing machining by milling was executed to the cutting speeds of 60, 80 e 100 m/min for the carbide inserts and to 700, 800 and 900 m/min to the ceramic inserts (HSM). Results obtained reveal that it was possible to accomplish the VAT 32® superalloy machining through milling within standard surface quality ranges, to both cutting tools applied. The aluminabased ceramic inserts allowed satisfactory roughness results (Ra 0.734 µm) associated to similar wear per cutting length results Vb*1000/Lc (0.015) in comparison to the coated carbide inserts. The Al2O3-MgO inserts are recommended for machining the VAT 32® at speeds of 900 m/min and low feed of 0.05 mm/t due to its high chemical stability and hardness, allowing the production of shear type chips. The coated carbide tools presented a superior performance to machine the VAT 32® by milling, being the best roughness (Ra 0.608 µm), flank wear Vb (0.125 mm) and Vb*1000/Lc (0.010) results found to the cutting speed of 60m/min and feed of 0.10mm/t, that generate segmented chips with loose arc form, excellent for good handling and disposal.

Nas últimas duas décadas a indústria metalúrgica de fabricação de superligas tem possibilitado diversas inovações de alto impacto na indústria metal mecânica. Entretanto, atualmente, essas indústrias tem tido que lidar com os vários desafios técnicos e comerciais impostos pelas atuais rígidas regulações de normas ambientais. Portanto, com o objetivo de satisfazer uma nova série de normas ambientais mais restritiva, a nova superliga de níquel intermediária designada VAT 32® foi desenvolvida para a aplicação em válvulas automotivas de alta performance. A superliga VAT 32® apresenta alta resistência ao desgaste à altas temperaturas aliada a custos de produção mais baixos se comparados às superligas aplicadas tradicionalmente. No entanto, devido à sua composição química e microestrutura, sérias dificuldades são observadas durante o processo de usinagem, diminuindo sua usinabilidade e limitando sua aplicação. Portanto, com o objetivo de estudar a usinabilidade desta nova superliga VAT 32® pelo processo de fresamento, o presente trabalho de pesquisa avaliou a aplicação de ferramentas de corte cerâmicas experimentais compostas de alumina dopada com óxido de magnésio (Al2O3-MgO), desenvolvidas pelo grupo de pesquisa do Departamento de Materiais e Tecnologia da UNESP, em comparação com ferramentas de corte comerciais de metal duro revestidas com TiAlN-TiN pelo método PVD. As variáveis de saída do processo de usinagem analisadas foram: a potência consumida, vibração, emissão acústica, qualidade da superfície resultante (rugosidade Ra, Rt e Rz), desgaste e avariais da ferramenta de corte, mecanismos de formação dos cavacos e a pressão específica de corte média (Ksm). Para avaliar os principais efeitos na usinagem, foi aplicada a análise de variância (ANOVA) e testes de normalidade, conduzidos de acordo com o delineamento de experimentos pela metodologia fatorial completo. O fresamento foi realizado sem lubrificação e com aplicação de velocidades de corte de 60, 80 e 100 m/min para as ferramentas de metal duro e 700, 800 e 900 m/min para as ferramentas cerâmicas (HSM). Os resultados obtidos revelam que foi possível realizar com sucesso a usinagem por fresamento da superliga VAT 32® com rugosidade dentro das faixas de qualidade superficial padrão para as duas ferramentas de corte aplicadas. As pastilhas experimentais de cerâmica possibilitaram obtenção de baixa rugosidade média (0.734 µm) associada a um desgaste específico Vb*1000/Lc (0.015) semelhante ao obtido em comparação às pastilhas de metal duro revestidas (0.010). As pastilhas Al2O3-MgO podem ser recomendadas para a usinagem do VAT 32® em velocidades de 900 m/min e baixo avanço de 0,05 mm/dente devido à sua alta estabilidade química e dureza, com produção de cavacos de cisalhamento. As ferramentas de metal duro revestido apresentaram alto desempenho aliado à baixa rugosidade média (0.608 µm) e desgaste de flanco Vb (0.125 mm) para a velocidade de corte de 60m/min e avanço de 0,10mm/dente com produção de cavacos segmentados com forma de arco solto que facilitam seu manuseio e descarte.
Análise da usinabilidade da superliga de níquel VAT 32® utilizando insertos comerciais e experimentais para fresamento
Keywords: Machining; Milling; Nickel Superalloy; Alumina-based tool; Coated carbide insert; HSM; Usinagem; Fresamento; Superliga de Níquel; Ligas Resistentes ao Calor; Ferramentas de corte